2011
DOI: 10.1007/s00264-011-1344-1
|View full text |Cite
|
Sign up to set email alerts
|

Osteosynthesis of femoral-neck nonunion with angle blade plate and autogenous fibular graft

Abstract: Angle blade plate provides rigid stability and offloads any shearing force over the fibular graft when used for revision internal fixation in aseptic femoral-neck nonunion. Thus, the fibular graft only serves the purpose of osteogenesis and stimulates the surrounding host cells to promote healing at the nonunion site. We recommend the angle blade plate and autogenous fibular graft as a viable option for hip-joint salvage in revision internal fixation of aseptic femoral-neck nonunion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…Various procedures with variable results have been reported. There is no standard protocol for choosing one over another for a particular fracture [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Various procedures with variable results have been reported. There is no standard protocol for choosing one over another for a particular fracture [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the manuscript by Sen et al entitled "Osteosynthesis of femoral-neck nonunion with angle blade plate and autogenous fibular graft" [1]. I must congratulate the authors for this study.…”
mentioning
confidence: 96%
“…It converts the vertical shear force into a horizontal compressive force and promotes union. However, it alters the biomechanics of the hip joint and causes shortening, limp and a decreased range of movement, probably because of increased pressure on the femoral head leading to degenerative disease or osteonecrosis [1,2]. Considering the long-term problems of osteotomy, Roshan et al suggested that bone grafting with internal fixation is still the reliable method of fixation in femur neck nonunion [2].…”
Section: Valgus Intertrochanteric Osteotomy May Be Consideredmentioning
confidence: 99%
“…An appropriately fixed angled blade plate would be definitely superior to cannulated screws fixation in terms of mechanical stability when used along with the fibular graft in femoral neck nonunion [1,5].…”
Section: Valgus Intertrochanteric Osteotomy May Be Consideredmentioning
confidence: 99%